Nationwide expansion of a financial incentive program on fruit and vegetable purchases among Supplemental Nutrition Assistance Program participants: A cost-effectiveness analysis. (December 2015) - An, Ruopeng
Abstract: High prices remain a formidable barrier for many people, especially those of low socioeconomic status, to adopt a healthier diet. The Food, Conservation, and Energy Act of 2008 mandated the U.S. Department of Agriculture (USDA) to conduct a pilot study to assess the impact of making fruits and vegetables more affordable for households in the Supplemental Nutrition Assistance Program (SNAP). Based on the USDA final report of the Healthy Incentives Pilot (HIP), a large-scale randomized trial in 2011–2012 that provided 30% rebate on targeted fruits and vegetables to 7500 study participants enrolled in the SNAP, we constructed a decision model to evaluate the cost-effectiveness of an expansion of the HIP to all SNAP households nationwide. The estimated life-time per capita costs of the HIP to the Federal government is $1323 in 2012 U.S. dollars, and the average gains in quality-adjusted life expectancy to a SNAP participant is 0.082 quality-adjusted life year (QALY), resulting in an incremental cost-effectiveness ratio (ICER) of $16, 172 per QALY gained. Sensitivity analysis using Monte Carlo simulations indicates a 94.4% and 99.6% probability that the estimated ICER would be lower than the cost-effective threshold of $50, 000 and $100, 000 per QALY gained, respectively. Moreover, the estimated ICER of the HIP expansion tends to be competitive in comparison to other interventions that aimed at promoting fruit/vegetable intake among adult population. Findings from this study suggest that a nationwide expansion of the HIP is likely to nudge SNAP households towards purchasing and consuming more targeted fruits and vegetables. However, diet behavior modification is proportional to price change. When people's actual eating behaviors and what dietary guidelines recommend differ by several folds, even a 30% rebate closes just a small fraction of that gap and has limited beneficial impact on participants' weight management, disease prevention, and health-related quality of life. Highlights: Healthy Incentives Pilot (HIP) offers SNAP households 30% rebate on produce purchase. We assess the cost-effectiveness of HIP expansion to all SNAP households nationwide. The estimated cost-effectiveness ratio is well below commonly adopted thresholds. HIP expansion would increase SNAP households' fruit/vegetable purchase and intake. Beneficial effect is only modest as behavior change is proportional to price change.